Assessing the efficiency of industrial wastewater plant of Basra Gas Company (University of Thi-Qar Journal for Engineering Sciences, 2023)
An important step in the avoidance of pollution was traditionally assuming the treatment of industrial effluent. As a result, it is crucial to regularly monitor and assess wastewater treatment facilities. This study examined the efficiency of an industrial wastewater treatment plant of a Gas Company in northern Rumelia. Several samples from the plant's outlet were collected for this purpose, and nine indicators (PH, EC, TDS, SO4, Turbidity, Total Hardness, Total Bacteria, BOD5, and COD) were tested. The results of these tests were compared to the guidelines established by Iraqi Health Ministry under Law No. 25 of 1967. Two samples were taken monthly from November through March 2022 for this study. The results showed that the majority of the indicators were above Iraqi standards, with values for PH ranging from (7-8.4), EC (1680-4060 mhos/cm), TDS (1206-2890 mg/l), SO4 (360-720 mg/l), turbidity (32-70 NTU), total hardness (655-779 mg/l), total number of bacteria (245-390 cell/ml), COD (110-227 mg/l), and BOD5 (57.9-119.5). The gas company's industrial wastewater treatment plant was unable to remove pollutants from the wastewater as a result. This is because there are no secondary or biological treatment components in the treatment plant; only primary treatment components are there.